2021
DOI: 10.1063/5.0042831
|View full text |Cite
|
Sign up to set email alerts
|

Energy dissipation mechanism of a centrifugal pump with entropy generation theory

Abstract: From the numerical calculations of a common centrifugal pump, the energy loss characteristics have been investigated by applying entropy generation theory to examine the loss due to the direct, turbulence, and wall friction dissipation rates. The turbulent and wall friction entropy dissipations contribute higher values compared with the direct entropy dissipation rate. The turbulent and wall friction entropy dissipations yielded 54.629% and 44.654%, respectively, at the design flow rate; however, the direct en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Therefore, the RNG k-ε model was selected. The viscous dissipation value is considerably smaller than the turbulent dissipation value [10,20], as discussed in the numerical result analysis. The power loss and location of loss production regions must be defined in machines.…”
Section: Entropy Production Methodsmentioning
confidence: 78%
See 3 more Smart Citations
“…Therefore, the RNG k-ε model was selected. The viscous dissipation value is considerably smaller than the turbulent dissipation value [10,20], as discussed in the numerical result analysis. The power loss and location of loss production regions must be defined in machines.…”
Section: Entropy Production Methodsmentioning
confidence: 78%
“…At part and design load conditions, minimal and moderate fluctuations of 0.5 and 9% were achieved in the value of the head coefficient, respectively [7]. In contrast, the pump efficiency exhibited deviations of 0.7, 4, and 8% between the simulation and experimental results for the design load, part load, and overload conditions, respectively [9][10]. At the duty flow, the efficiency and head coefficient deviations were in reasonable ranges.…”
Section: Experimental Test Setupmentioning
confidence: 88%
See 2 more Smart Citations
“…Yu et al [ 4 ] calculated the hydraulic loss of the Francis turbine under different mass flow rates based on entropy production theory and found that the energy loss of the draft tube of the Francis turbine was larger than that of other components. Huang et al [ 5 ] calculated the entropy of ordinary centrifugal pumps and found that the direct dissipation entropy in the pump was very low, accounting for only 0.716%. EPTD and EPWS accounted for 54.629% and 44.654%, respectively, indicating that the influence of average velocity in the pump was small, and the main flow loss was caused by turbulent flow and wall shear stress.…”
Section: Introductionmentioning
confidence: 99%